Legitimasi Islam: Sebuah Pembacaan Teoretis Tentang Wahyu Alquran - Ikhwan, Munirul (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2020)
In the studies of the Qur’an, there is no central concept as that of the Qur’anic revelation itself. The revelation becomes a symbol for God’s unique communication to humans through human agency, called a prophet. Studies on the Qur’anic revelation by classical Muslim scholars have stressed much on its metaphysical aspects, while modern scholars like Toshiko Izutsu begin offering theoretical readings of the Qur’anic revelation as a linguistic concept, i.e., metaphysical communication expressed in a certain language system. By reviewing the existing studies, this article pays special attention to the sociological significance of the revelation. This study examines how revelation as an act of God arises in a setting of human history, and the extent to which it must correspond and dialogue with the values, institutions, and socio-cultural systems of its first audience. This study sees that the power of the Qur’anic revelation lies in its ability to build legitimacy and to integrate its first audience into a broader horizon that allowed them to participate in the contestation of religious discourse with older religious communities.